Flow visualization in a Ranque-Hilsch vortex tube / Yusman Istihat ... [et al.] - Istihat, Yusman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
This paper presents the results of flow visualization in a Ranque-Hilsch vortex tube (RHVT). The RHVT has been newly designed and locally fabricated. Dimensional analysis and similarity was carried out by taking comparison between real model (Blue Model) of RHVT and prototype (Clear Prototype) using acrylic. The research objective is to visualize flow patterns inside the tube and water is chosen as the flowing fluid. Several methods of visualization were adapted in this exercise especially for observing the particles movement throughout the process. Still pictures and videos were recorded and formation of vortex was studied. It is observed that the flow pattern of circulation was presented and visible. The existence of two swirling flows can be seen and documented. The frames of pictures show a flow pattern of forward and backward flows obtained from the vortex tube.